PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (studi pada konsumenâRumah Makan Padang Mitraâ di Semarang) - Ginanjar Budi Santoso, 13.05.51.0137 (Students Journal of Economic and Management, 2017)
This study aims to determine how much influence the quality of the product, the perception of price and location to the purchase decision at Mitra Padang Semarang.After examination of literature and hypothesis examination, data from distribution of questionnaire of 100 consumers of Rumah Padang Mitra Semarang were obtained by using purposive sampling, then analyzed the data obtained by using quantitative analysis and reliability test, multiple regression analysis, hypothesis test And f test, and determination analysis (RÂ²).The result of the research shows that the result of determination seen in Adjusted R Square is 0, which means 62,1% of variation of Sales decision can be explained by Product Quality, Price and Location Perception variable. . That is not included in the research. Partially based on t test result of the variables in this research is positive and significant where price level has the biggest influence in this research variable, whereas location has the least influence to decision of purchase. Based on the results of F test shows simultaneously or together variables in this study that is the product, perception of prices, and significant and significant location to the purchase decision. Therefore, to improve purchasing decisions can be done by improving product quality, competitive pricing, and strategic location selection.Keywords: Profitability, purchasing decision, product quality, price perception,Location